2007
DOI: 10.1002/jpln.200622012
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of manure and fertilization on soil organic matter and quality parameters of a calcareous soil in NW China

Abstract: Long‐term applications of inorganic fertilizers and farmyard manure influence organic matter as well as other soil‐quality parameters, but the magnitude of change depends on soil‐climatic conditions. Effects of 22 annual applications (1982–2003) of N, P, and K inorganic fertilizers and farmyard manure (M) on total organic carbon (TOC) and nitrogen (TON), light‐fraction organic C (LFOC) and N (LFON), microbial‐biomass C (MB‐C) and N (MB‐N), total and extractable P, total and exchangeable K, and pH in 0–20 cm so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 32 publications
5
24
0
Order By: Relevance
“…Earlier research in China has shown substantial increase in extractable P and total P in soil with long-term annual applications of FYM [5]. In our study, extractable P in the surface soil also increased considerably with compost even after three annual applications.…”
Section: Soil Ph and Residual Available N P K And S In The Soil Prosupporting
confidence: 71%
See 2 more Smart Citations
“…Earlier research in China has shown substantial increase in extractable P and total P in soil with long-term annual applications of FYM [5]. In our study, extractable P in the surface soil also increased considerably with compost even after three annual applications.…”
Section: Soil Ph and Residual Available N P K And S In The Soil Prosupporting
confidence: 71%
“…Fertilization with organic amendments, such as compost manure/farm yard manure (FYM), alfalfa pellets/powder, distiller grain and thin stillage can have both direct (e.g., enhancing organic C in soil) and indirect (e.g., providing available nutrients after decomposition/mineralization) benefits on soil physical, chemical and biological properties, and crop yields [1][2][3][4][5][6][7][8][9]. Inorganic amendments and microbial inoculants, such as wood ash, rock phosphate, Penicillium bilaiae, MykePro, gypsum and elemental S, have been investigated for their potential as organic fertilizers in many studies, but their effectiveness to increase the availability of P or S in soil, and subsequently improve crop yield varies with nutrient source/type, severity of P, S and other nutrients deficiency in soil, soil type and climatic conditions [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil pH ranging from 5.40 to 5.68 was not significantly different across all treatments, indicating that there was no noticeable effect of fertilizers on soil pH after 5 yr of continuous annual fertilizer applications. Yang et al (2007) and Gu et al (2009) also reported that inorganic fertilizer and organic amendment had no effect on soil pH after 22 yr of continuous annual fertilizer applications. However, Shen et al (2010) and Hu et al (2011) showed that inorganic and organic fertilization significantly decreased soil pH after long-term fertilizer applications.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have focused on fertilization regimes on soil fertility Liu et al, 2010), crop yields (Venkatesan et al, 2004;Zhu et al, 2007) and microbial communities (He et al, 2008;Shen et al, 2010), but, up to now, the results of these reports are still not unanimous, and even conflicted. Moreover, most studies were concerned about the soils for growing food crops, like rice (Wu et al, 2011), wheat (Shen et al, 2010), maize or their combination for rotation (Kumar and Yadav, 2001;Yang et al, 2007;Hu et al, 2011), while few about the soils for planting tea (Venkatesan et al, 2004). Hence, it is necessary to examine the effects of fertilization regimes on tea yields, soil fertility, and microbial communities.…”
Section: Introductionmentioning
confidence: 99%